Oropharyngeal exercises as adjunct therapy to the management of obstructive sleep apnea - Chye, Gan Boon (2018)
Introduction Obstructive sleep apnea (OSA) can be treated with weight reduction through diet and exercise, usage of intraoral lingual retainer and mandibular advancement device and continuous positive airway pressure (CPAP) machine. Most common operations such as adenotonsillectomy can reach only about 50% effectiveness. Due to the difficulty in losing substantial weight, financial factor in getting CPAP machine as well as high risk for operative procedures, there is a role for a more favorable alternative treatment such as oropharyngeal exercises. Oropharyngeal exercises consist of 4 tongue exercises, 1 soft palate exercise and 5 facial muscles exercises that will increase the tone of oropharyngeal and tongue muscles that collapse during sleep after 3 months of exercises. Objectives To determine the effectiveness of oropharyngeal exercises as an adjunct therapy in the management of OSA. Methodology A prospective randomized controlled trial study was carried out on age 18 to 80 years old patients with confirmed diagnosis of OSA through PSG in Hospital Sultan Abdul Halim, Sungai Petani, Kedah from March 2016 to February 2017. Fifty consented OSA patients who fulfilled inclusion criteria were randomized into 2 groups, where therapy group of patients were taught oropharyngeal exercises while the control group were taught deep breathing exercises. After 3 months of 3 times daily exercises, patient will bereassessed by repeat interview using Epworth Sleepiness Scale, Thornton Snoring scale, flexible scope with Muller’s maneuver and subsequently repeat PSG with blinded sleep technician. Result There was no significant changes in control group of 25 patients. In the group that performed oropharyngeal exercises, there were significant reduction of Epworth Sleepiness Scale and Thornton Snoring Scale scored (p = 0.001 and p < 0.001) respectively. There was improvement in modified Mallampati grading (p = 0.030). Flexible endoscopy with Muller’s maneuver also showed reduction of collapse over retropalatal level (p = 0.022). In PSG, the apnea-hypopnea index showed significant reduction (p < 0.001). Conclusion Oropharyngeal exercises significantly improve snoring, daytime somnolence and lifestyle based on subjective scoring from questionnaires and objective measurement through scope findings and PSG results. Oropharyngeal exercises can be used as an alternative or adjunct therapy in the management of OSA.